SUPPORT LEMBAGA KEUANGAN SYARIAH DALAM KEMANDIRIAN EKONOMI MASYARAKAT DESA - Nurintan Siregar (EKSYA : Jurnal Ekonomi Syariah, 2023)
Islamic financial institutions are icons of a country's welfare. Financial institutions function to create community welfare wherever they are. This research aims to find out how Islamic Financial Institutions support in providing and support the independence of rural communities. This research uses a descriptive qualitative method, with a literature approach. The data collected comes from literature relevant to the research. The results of this study are that Sharia Financial Institutions (LKS) are financial institutions that operate by Islamic economic principles or sharia law. These principles include the prohibition of usury (interest), excessive speculation (maisir), unclear transactions (gharar), and the prohibition of business activities involving haram elements (prohibited in Islam). The development of Islamic financial institutions directly or indirectly realizes the economic independence of rural communities which influences national economic development and growth. The role of Islamic financial institutions in the economic activities of the community, especially in realizing the economic independence of rural communities, includes the transfer of assets, transactions, liquidity, and efficiency. With the existence of Islamic financial institutions, the economy of rural communities can develop well because it can be used as a place to obtain financial support so that it is more productive and independent, for the realization of the welfare of rural communities, and this is the goal and strategic plan of the government.